MEMBINGKAI KIAT GEREJA DALAM BERINTERAKSI SOSIAL DENGAN MASYARAKAT DALAM MENJANGKAU JIWA DI ERA DIGITAL: STUDI KASUS GBI TABGHA BATAM - Agave Purba, Osaca Yeremia; Ompusunggu , Irma; Lidiah, Lidiah (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
The advancement of digital technology has brought significant transformation to society, including in the realm of religious practice and church ministry. Churches are required to adapt wisely to remain relevant and actively engage within the dynamic digital society. This study aims to analyze the church’s role and strategies in interacting with the social community in the digital era, focusing on the digital ministry implementation at GBI Tabgha Batam. The research employed a qualitative approach through literature study and interviews to understand firsthand experiences of church ministers involved in digital transformation. The findings reveal that GBI Tabgha Batam successfully utilized digital technology to expand its spiritual and social outreach through enhanced digital literacy, development of interactive platforms, hybrid worship services, and creative dissemination of spiritual materials. The church also maintains ethical and digital security standards in managing congregation data and reporting social programs such as Cahaya Obor Berkat (COB) and Start2B. These findings affirm that digitalization is not merely a technical adaptation but an integral part of the church’s theological calling to embody Christ’s love and transformation in the modern world. By implementing ethical and well-structured digital strategies, the church can strengthen its relevance, expand social impact, and build an inclusive faith community in the digital era.